When workaholism is negatively associated with burnout: A moderated mediation - Makhdoom, Irsa Fatima; Malik, Najma Iqbal; Atta, Mohsin; Malik, Nudra; Qureshi, Madeeha Gohar; Shahid, Muhammad; Tang, Kun (Frontiers in Public Health, 2022)
Aim Previous theory and research postulate that workaholism is one of the important factors that contribute to burnout. The present study aimed to analyze the role of psychological capital as a mediator between the two. Moreover, the study examined the moderating role in the stated mediated relationship. Methods The researchers approached a sample of university teachers (N = 1,008) including both male (n = 531) and female (n = 477) university teachers by using a multi-stage random sampling technique. For this purpose, DUWAS-10 Oldenburg Burnout Inventory, Challenging Job Demands Scale, and Anila PsyCap Scale were applied to measure workaholism, burnout, challenging job demands, and PsyCap, respectively. The data obtained from the sample was subjected to analysis by using Model 14 of Process Macro by Hayes. Results The results confirmed the mediating role of PsyCap and moderating role of time pressure and cognitive demands in the relationship of the two variables. The results concluded that workaholism is not directly related to burnout rather the negative relationship existed through psychological capital, and the mediated relationship was stronger for the university employees who were to face a higher level of challenging job demands including cognitive demands and time pressure. Conclusion Burnout is an occupational health problem that causes devastating effects on both the employees as well as to the organizational economy. Improving personal resources might help the negative relationship between workaholism and burnout in higher education institutions in the country.